Playing bit parts in Shakespeare - Mahood, M. M. (Molly Maureen) (Routledge, 1998)
A unique survey of the small supporting roles, such as foils, feeds, attendants and messengers, that feature in Shakespeare's plays, exploring the various functions of these roles. Includes a new appendix, 'Who Says What?' and a character index.